Berberine Improves Irinotecan-Induced Intestinal Mucositis Without Impairing the Anti-colorectal Cancer Efficacy of Irinotecan by Inhibiting Bacterial β-glucuronidase - Yue, Bei; Gao, Ruiyang; Lv, Cheng; Yu, Zhilun; Wang, Hao; Geng, Xiaolong; Wang, Zhengtao; Dou, Wei (Frontiers in Pharmacology, 2021)
Irinotecan (CPT11), a broad-spectrum cytotoxic anticancer agent, induces a series of toxic side-effects. The most conspicuous side-effect is gastrointestinal mucositis, including nausea, vomiting, and diarrhea. A growing body of evidence indicates that bacteria β-glucuronidase (GUS), an enzyme expressed by intestinal microbiota, converts the inactive CPT11 metabolite SN38G to the active metabolite SN38 to ultimately induce intestinal mucositis. We sought to explore the potential efficacy and underlying mechanisms of berberine on CPT11-induced mucositis. Our study showed that berberine (50 mg/kg; i.g.) mitigated the CPT11-induced loss of mucosal architecture, ulceration, and neutrophil infiltration. Meanwhile, berberine improved mucosal barrier function by increasing the number of globlet cells, protecting trans-endothelial electrical resistance (TEER), reducing permeability and increasing tight junction proteins expression. LC-MS analysis showed that berberine decreased the content of CPT11 and SN38 in feces, which correlated with decreases in both GUS activity and GUS-producing bacteria. Further molecular docking and Lineweaver-Burk plots analyses suggested that berberine functions as a potential non-competitive inhibitor against GUS enzyme. Of note, berberine maintained the anti-tumor efficacy of CTP11 in a tumor xenograft model while abrogating the intestinal toxicity of CPT11. Overall, we identified for the first time the remission effects of berberine on intestinal mucositis induced by CPT11 without impairing the anti-colorectal cancer efficacy of CPT11 partially via inhibiting bacterial GUS enzyme.